Misconception of reading literacy and its impacts on literacy acculturation in school - Fauzan Fauzan; Ribut Wahyu Eriyanti; Ria Arista Asih (Jurnal Cakrawala Pendidikan, 2023)
Literacy competencies are important for students to keep abreast of the pace in the 4.0 industrial age. Misunderstanding of the concept of literacy may result in the incorrect application of literacy acculturation. This study is aimed at 1) describing teachers’ misconceptions of reading literacy and 2) describing the implementation of students’ reading literacy acculturation at school. Data were collected from teachers’ and students’ statements and activities during the literacy acculturation activities in the participating schools from 19 regencies in East Java, Indonesia. Additional data were in the forms of documents and field notes obtained from observation, interviews, questionnaires, and documentary studies. The results show that: 1) the concept of literacy is understood as literal and mechanistic reading, and 2) schools tend to apply formal literacy activities by asking students to read texts 15 minutes before classes begin. Several problems are found in most research sites in which there is no follow-up on the given free reading assignments, teachers and school principals neither become literacy models, the availability of fiction and non-fiction books is limited, and students are not highly motivated to follow the reading literacy program. This study implies the urgent need to improve all school stakeholders understanding of the literacy concept and provide better activities for the implementation of the reading literacy acculturation program in schools.